"One aspect of the coaching business." Function and role of sports physiotherapists from the perspective of coaches in German elite athletics. Issue 3 (1st September 2020) - Steinmann, Annika; Jaitner, David; Himmelseher, Nadja
ABSTRACT: According to social differentiation theory, professional activity of elite sports physiotherapists is characterised by potential conflict between the social logics of the medical sector and elite sports. Sports physiotherapists in Germany are part of the medical sector. By their work, they prevent illness and promote health. However, within the context of elite sports they run the risk of being instrumentalised for achieving victories in athletic comparisons. Using a reconstructive hermeneutic approach, the present study explored the function and role expectations of sports physiotherapists from the perspective of professional coaches engaged in elite athletics. Four semi-structured interviews were conducted. Two main themes were identified: 1) Attributed tasks and expected physiotherapeutic effects, 2) expectations on the physiotherapeutic time arrangement. Findings suggested that the narratives of the coaches were mostly bound to the agonal logic of elite sports and mainly designated sports physiotherapists as performance enhancers over health.